Characterization and Treatment of Some Municipal Sludges - Kumar, Vinod (My University, 2009)
Based on the study performed on characterization and treatability of some sludges, the following conclusion were made- 1. The raw sludge at STP-1 and STP-2 has favorable pH, adequate nutrients etc. This could be a source of fertilizer for agriculture/soil conditioner. 2. Raw sludge at STP-2 has more objection than that of STP-1 (although my results couldn’t reveal). The municipality needs to play more attention during waste treatment and ultimate disposal. 3. Sludge drying bed is a better treatment option for enhancing the quality of raw sludge in comparison to centrifugation. More emphasis is required for popularizing the same. In a nut shell, improving sludge quality is a necessity for the city municipality prior to the ultimate disposal. Economical & viable methods of sludge treatment are to be devised.
Keywords: Sludge; Municipal; Treatment; Characterization